Legal issues connected with the obligations of a real estate purchaser resulting from Article 2b of the Act on shaping the agricultural system - Blajer, Paweł A. (Przegląd Prawa Rolnego, 2021)
The aim of the considerations was to resolve doubts regarding the interpretation of the provision of Article 2b of the Act of 11 April 2003 on shaping the agricultural system. This provision imposes, in principle, two universal obligations on each acquirer of agricultural real estate (i) to run an agricultural holding contained in the agricultural real estate acquired, for a period of at least 5 years from the date of acquisition, or, in the case of a natural person, to run the holding personally, and (ii) not to dispose of the acquired real estate or give it in possession to other entities within the same 5-year period. The analysis of this provision enabled to identify many practical problems, and to formulate substantial reservations as to its compliance with the fundamental principles of the Constitution of the Republic of Poland and European Union law. As a consequence, de lege ferenda comments have been formulated, calling for a far-reaching modification of this regulation or its removal altogether from the Polish agricultural law system.